Early parenting intervention promotes 24‐month psychomotor development in preterm children. (3rd June 2020) - Pisoni, Camilla; Provenzi, Livio; Moncecchi, Michela; Caporali, Camilla; Naboni, Cecilia; Stronati, Mauro; Montirosso, Rosario; Borgatti, Renato; Orcesi, Simona
Abstract: Aim: Although parenting is key to promoting healthy development of at‐risk preterm infants, parents have often restricted access to neonatal intensive care units (NICUs). This study aimed to assess the effect of an early parenting intervention on the psychomotor outcome in preterm children at 24 months of corrected age. Methods: Forty‐two preterm children and their parents were consecutively recruited at a level III NICU in Northern Italy and randomly allocated to early intervention (two educational peer‐group sessions and four individual infant observation sessions) or care as usual (no educational or infant observation sessions). During NICU stay, parents provided information on daily holding and skin‐to‐skin. Psychomotor development was measured at 24 months of corrected age using the Griffith Mental Development Scales. Results: There were no significant differences in socio‐demographic and clinical variables between early intervention (n = 21; 13 females) and care as usual (n = 21; 12 females) groups. At 24 months of corrected age, children in the early intervention arm had greater scores for global psychomotor development as well as for Hearing‐Speech and Personal‐Social sub‐scales, compared to those in the care as usual group. Conclusion: The present NICU parenting intervention was found to be associated with better psychomotor outcomes in preterm children at 24‐month age. The effects were especially evident for domains related to language and socio‐emotional functioning. Results are promising and should be retested with more heterogeneous and representative preterm sample.